Numerical Investigation of Intermittent weld Fillet in T – Section Structure – A Comparison with Continuous Weld - Ameen, Sameer Hashim (Nahrain University College of Engineering Journal, 2014)
In current work, theoretical investigation of two perpendicular plates (joint by a double weld fillets) form a T – section structure made from plain carbon steel was carried out using AUTODESK INVENTOR PACKAGE. The intermittent weld in its two types (stagger and chain) was taken as fastening element in present work. The numerical results (stresses, deformations, and safety factors) were evaluated and compared with continuous weld results. The stagger weld, namely 80(20) arrangement, was being investigated as best arrangement among other arrangements which developed scientific reduction in shear stresses at yz- and xy-plane against chain weld by 15.78 % and 37.86 % respectively. The percentage reduction of safety factors according to Von – Misses stress of 80(20) chain and stagger intermittent welds are 29.78 % and 16.2 % in comparison with continuous weld respectively. The stagger intermittent weld 80(20) is gives lower stresses developed in welded section with higher safety factor.